Teacher Professionality Development Strategy in Basic Education Units Based on Independent Learning-Teaching Policy - Zuliana Zuliana; Nurul Zahriani Jf; Muhd. Hayyanul Damanik (STAI Serdang Lubuk Pakam, 2022)
Freedom to learn and teaching is a priority policy for the ministry of education in improving the quality of education. Of course there are many things that must be adjusted to this policy, including the professional development of teachers. Because there are many educational units that have not harmonized them. This study aims to analyze teacher professionalism development strategies based on the independent learning policy, and the obstacles they face. This research was conducted at SDIT Zia Salsabila as a school that implements an independent learning policy. The research method used is qualitative with a case study approach. The results of the study show that independent learning-based teacher professional development is divided into four keys, namely independence, competence, collaboration, and career. The development strategy is humanizing relationships, understanding concepts, building sustainability, choosing challenges, empowering contexts. The obstacles faced in the professional development of teachers are the lack of socialization by the government regarding the independent learning policy, the emergence of negative perceptions about the orientation of the independent learning policy, the lack of understanding of the concept of independent learning, the absence of driving teachers, low teacher competence, especially teacher who is still a student.